ผลิตภัณฑ์สมุนไพรปรับอากาศเพื่อยับยั้งการเจริญของแบคทีเรียบางชนิดที่ก่อโรคในระบบทางเดินหายใจมนุษย์ - วนิดา เล่าซี้ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Twenty - one medicinal plants were solvent extracted using ethanol 95% and water, and were volatile oil extracted. The crude extracts and volatile oils were further tested for their growth inhibitory effect on four respiratory tract pathogenic bacteria including Corynebacterium diptheriae, Legionella pneumophila DMST 12800, Streptococcus pneumoniae ATCC 49619 and S. pyogenes by agar disc and well diffusion methods. Results showed that the volatile oils of Citrus limon L. and ethanolic extracts of Michelia champaca L. were able to inhibit growth of all pathogenic bacteria. Examining for MIC using a broth dilution method showed that the volatile oil of Citrus limon L. and ethanolic extracts of Michelia champaca L. possessed the lowest value of MIC against all four respiratory tract pathogenic bacteria. Volatile oil of Citrus limon L. and ethanolic extract of Michelia champaca L. were further used to develop air freshener gel and spray products, respectively. Both products were able to inhibit growth of four respiratory tract pathogenic bacteria with the given zone of inhibition ranging between 9-23 mm. The Citrus limon L. air freshener gel and the Michelia champaca L. air freshener spray showed the cytotoxicity against Vero cells with CD50 of 0.56 and 0.20 mg/ml, respectively. The products were not able to store at high temperature as the physical appearance was altered and the efficiency was decreased resulting in shortening the shelf-life. The products were stable for 3 months when kept at 4-25°C.